Sternal wound tuberculosis following cardiac operations: a review - Yuan,Shi-Min (2015)
Abstract Objective: The diagnosis and treatment of sternal wound infections with mycobacteria are challenging. Such an infection is often associated with a delayed diagnosis and improper treatment that may lead to a worsened clinical outcome. The present study is designed to highlight its clinical features so as to facilitate a prompt diagnosis and timely treatment. Methods: MEDLINE, Highwire Press, and Google search engine were searched for publications in the English language, with no time limit, reporting on sternal wound infection caused by tuberculosis after cardiac surgery. Results: A total of 12 articles reporting on 14 patients were included in this study. Coronary artery bypass grafting was the underlying surgical procedure in more than half of the cases. Purulent discharge and cold abscess were the two main presenting symptoms. Diagnosis of sternal wound infection was evidenced in all 14 patients by different investigations, with culture of samples being the most sensitive method of identifying the pathogen. Good response to first-line anti-tuberculous agents was noted. Almost all patients required surgical debridement/resection and, sometimes, sternal reconstruction. A delayed diagnosis of sternal wound infection may lead to repeated recurrences. A comparison between patients with sternal wound infection due to tuberculosis and non-tuberculous mycobacterial infections showed that the former infections took an even longer period of time. Comparisons also revealed patients with sternal tuberculosis infection had a significantly higher mortality than patients with sternal non-tuberculous infection (29.2% vs. 0%, P=0.051). Conclusion: Sternal infection caused by tuberculosis after cardiac surgery has a longer latency, better response to first-line drugs, and better outcomes in comparison with non-tuberculous sternal infection. Early diagnosis and early anti-tuberculous treatment can surely improve the patients' prognosis.